(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The goal of most countries is the desire to maintain a stable price level of goods and services. This however, appears to be an uphill task given the incidence of subsidy removal that is presently ravaging the developing economies of the world. The study aimed at establishing a relationship between subsidy removal and construction material, and labour prices. To achieve the aim, a survey design approach was conducted. Data was obtained in other to get the prices of the construction materials and wages paid to labourers, through quarterly prices of construction materials from Nigeria Institute of Quantity Surveyors (NIQS) published journals, Fobis International Market, and Ogidi Building Material Markets, Onitsha, Anambra State. Meanwhile, Descriptive statistics and a multiple regression model were used to analyze the data collected. It was discovered that subsidy removal in Nigeria has been far from stable, and has affected material and labor prices non-uniformly and inconsistently. Hypotheses was also postulated; results shows that there is a significant relationship between building material prices and the subsidy removal in Anambra State and that subsidy removal does affect the labour costs, wages of skilled and unskilled labour, within Awka, Anambra State. The study finally concluded that Government should also ensure a steady supply of power from the power sector as against the epileptic power supply and reduce the increase in power tariff, repair the local refineries, and focus more on encouraging the local refining of petroleum products instead of importing them in order to reduce constant increase on our domestic prices for petroleum products and consequently inflation on the materials too.